Isotope studies of presolar silicon carbide grains from supernovae: new constraints for hydrogen-ingestion supernova models - Hoppe, Peter; Leitner, Jan; Pignatari, Marco; Amari, Sachiko (Monthly notices of the Royal Astronomical Society, 2024)
We report isotope data for C, N, Al, Si, and S of 33 presolar SiC and Si3N4 grains (0.3-1.6 $μ$m) of Type X, C, D, and N from the Murchison CM2 meteorite of likely core-collapse supernova (CCSN) origin which we discuss together with data of six SiC X grains from an earlier study. The isotope data are discussed in the context of hydrogen ingestion supernova (SN) models. We have modified previously used ad-hoc mixing schemes in that we considered (i) heterogeneous H ingestion into the He shell of the pre-SN star, (ii) a variable C-N fractionation for the condensation of SiC grains in the SN ejecta, and (iii) smaller mass units for better fine-tuning. With our modified ad-hoc mixing approach over small scales (0.2-0.4 M⊙), with major contributions from the O-rich O/nova zone, we find remarkably good fits (within a few per cent) for 12C/13C, 26Al/27Al, and 29Si/28Si ratios. The 14N/15N ratio of SiC grains can be well matched if variable C-N fractionation is considered. However, the Si3N4 isotope data point to overproduction of 15N in hydrogen ingestion CCSN models and lower C-N fractionation during SiC condensation than applied here. Our ad-hoc mixing approach based on current CCSN models suggests that the O-rich O/nova zone, which uniquely combines explosive H- and He-burning signatures, is favourable for SiC and Si3N4 formation. The effective range of C/O abundance variations in the He shell triggered by H ingestion events in the massive star progenitor is currently not well constrained and needs further investigation.